New Personalistic Philosophy Based on Hans Eduard Hengstenberg’s Interpretation of Max Scheler's System - Pasterczyk, Piotr (Verbum Vitae, 2020)
The article discusses the possibility of a new personalistic anthropology rooted in philosophia perennis and modern phenomenology, based on the thoughts of German anthropologist Hans Eduard Hengstenberg. Unlike Wojtyła and Stein, who did not create a new synthesis based on Husserl’s or Scheler’s phenomenology and the metaphysics of Thomas Aquinas, Hengstenberg was able to create an original concept of the human person involving metaphysical and phenomenological inspirations. It is personalism, based on the phenomenological theory of a spiritual act (Scheler) and the metaphysical theory of constitution (Plato, St. Augustine). According to Hengstenberg, the possibility of a new personalistic philosophy starts with a phenomenological analysis of three basic attitudes of human behavior: consensual to the object of cognition and emotion, contrary to the object of cognition and emotion, and utilitarian. The metaphysical heart of Hengstenberg’s personalism forms the theory of the metaphysical constitution of the spirit, body and personalistic principle.